#1**+1 **

Simplify the following:

b/3 + (2 b)/3 - (5 (b + 1))/6

Put each term in b/3 + (2 b)/3 - (5 (b + 1))/6 over the common denominator 6: b/3 + (2 b)/3 - (5 (b + 1))/6 = (2 b)/6 + (4 b)/6 - (5 (b + 1))/6:

(2 b)/6 + (4 b)/6 - (5 (b + 1))/6

(2 b)/6 + (4 b)/6 - (5 (b + 1))/6 = (2 b + 4 b - 5 (b + 1))/6:

(2 b + 4 b - 5 (b + 1))/6

2 b + 4 b = 6 b:

(6 b - 5 (b + 1))/6

-5 (b + 1) = -5 b - 5:

(6 b + -5 b - 5)/6

Grouping like terms, 6 b - 5 b - 5 = (6 b - 5 b) - 5:

((6 b - 5 b) - 5)/6

6 b - 5 b = b:

**(b - 5)/6**

Guest Oct 3, 2017